Strange Vernaculars How Eighteenth-Century Slang, Cant, Provincial Languages, and Nautical Jargon Became English - Sorensen, Janet (Princeton University Press, 2017)
How vocabularies once associated with outsiders became objects of fascination in eighteenth-century BritainWhile eighteenth-century efforts to standardize the English language have long been studied-from Samuel Johnson's Dictionary to grammar and elocution books of the period-less well-known are the era's popular collections of odd slang, criminal argots, provincial dialects, and nautical jargon.